PENGARUH PROFITABILITAS TERHADAP KEBIJAKAN UTANG MELALUI KEBIJAKAN DEVIDEN (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR PADA BEI TAHUN 2015-2017) - Muammar Khaddafi; Eggy syahputra (Department of Accounting, Faculty of Economics & Business, 2019)
This study aimed to determine the Effect of Profitability directly or indirectly on Debt Policy through Dividend Policy on Manufacturing Companies listed on the Stock Exchange in 2015-2017. This study used secondary data in the form of financial statements of Manufacturing Companies listed on the Stock Exchange in 2015-2017 which were accessed on ww.idx.com. The study population was 851 manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. The sample is 38 companies selected using the Purposive sampling method. This quantitative study used path analysis to analyze the data with the help of SPSS 16.0. The results showed that profitability negatively influenced debt policy, dividend policy did not influence debt policy, and profitability negatively influenced the dividend policy of manufacturing companies.